Capsular Complications and Subsequent Instability on the Rise as Indications for Revision Hip Arthroscopy (140). Issue 10 (31st October 2021) - Selley, Ryan; Lawton, Cort; Dooley, Matthew; Swensen, Stephanie; Marom, Niv; Kelly, Bryan; Ranawat, Anil; Nawabi, Danyal
Objectives: Femoroacetabular impingement (FAI) has become an increasingly recognized diagnosis contributing to morbidity in the adolescent and young adult population over the past decade. Our ability to treat such pathology with hip arthroscopy has grown in parallel. As the number of hip arthroscopy cases performed annually continues to rise, so will the number of patients be requiring revision surgery. Continuing to reassess trends in the indications for revision hip arthroscopy is critical to improve primary surgery techniques and accurately address pathology at the time of revision surgery. As such, the purpose of this study is to determine the trends in indications for revision hip arthroscopy. Methods: A single-center hip preservation registry was reviewed to identify patients who underwent revision hip arthroscopy for the treatment of femoroacetabular impingement between 2012 and 2019. Patient demographics and primary indications for revision hip arthroscopy were determined. Trends in the indications for revision hip arthroscopy were compared. Results: A total of 229 patients met inclusion criteria for this study. Residual FAI in our cohort was the primary indication for revision with 68.1% of cases and remained the primary indication for revision in all years of the study (Figure 1). The second most common indication for revision was instability at 14.8%, third heterotopic ossification (HO) at 4.8% and fourth was adhesions at 3.9% (Table 1). In cases in which instability was present, 39.4% were secondary to traumatic capsular deficiency, 34.2% were attributed to atraumatic capsular deficiency and 26.3% were attributed to borderline dysplasia, Numerous other findings were noted at the time of revision arthroscopy, 100% of patients were noted to have synovitis, in 97.8% loose osteochondral fragments were noted, 90.8% had labral tears, 47.6% had adhesions and 24.5% had heterotopic ossification (Table 2). Conclusions: The most common indication for revision hip arthroscopy in the treatment of FAI remains residual impingement. However, capsular complications are increasingly recognized as an indication for revision hip arthroscopy highlighting the need for careful attention to capsular management, post-operative protection during the healing period, and preoperative recognition of hip instability. Lastly, heterotopic ossification is third most common reason for revision hip arthroscopy underlining the importance of postoperative prophylaxis.